ANALISIS PERTIMBANGAN HAKIM DALAM MEMUTUS PERKARA TINDAK PIDANA KESEHATAN (STUDI PUTUSAN NOMOR 14/PID.SUS/2021/PN PTI) - Ana Pristiwijayani; Itok Dwi Kurniawan (Sebelas Maret University, 2023)
Abstract: The research conducted by the author aims to determine the consider of judges in a rule deciding criminal cases by deliberately producing or distributing pharmaceutical preparations without a marketing license and the consider (verdict study Number: 14/Pid.Sus/2022 / PN Pti). This type of legal research is normative legal research and prescriptive and applied. The research approach uses a case approach. Legal materials used include primary and secondary legal materials. The technique of collecting legal materials used is the study of literature. The analysis used is syllogism deduction. Based on the results of the study showed that, first, the position of pharmacologists compared to other evidence is the same as long as the conditions as valid evidence are met. Second, the consideration of the District Court judge in examining and deciding the criminal case by the defendant Ahmad Nur Muchlisin is following Article 183 of the Criminal Procedure Code because it has met at least two valid pieces of evidence, and the pharmacologist's statement does not have a binding evidentiary force value. Keywords: Health Crimes; Trihexyphenidyl; Evidence; Judge’s Consideration